Profile of Student Career Commitments Based On Batak Subculture - Lesmana, Gusman (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2020)
The article aims to describe the results of the analysis of career commitment based on five Batak subcultures namely; Karo Batak, Mandailing Batak, Toba Batak, Pakpak Batak, and Simalungun Batak at the Faculty of Education, Muhammadiyah University of North Sumatra enrolled in the 2019/2020 school year. Description of this career commitment using the instrument used is a measurement tool and predictions of Gary J. Blau's career commitment. This article is expected to contribute to the development of knowledge in multicultural fields, especially cross-cultural fields in guidance and counseling services. The results of this study can be used for the purposes of developing the science of guidance and counseling in the study of multicultural competencies both conceptually and practically.